2012
DOI: 10.1289/ehp.1104458
|View full text |Cite
|
Sign up to set email alerts
|

Placental Mitochondrial DNA Content and Particulate Air Pollution during in Utero Life

Abstract: Background: Studies emphasize the importance of particulate matter (PM) in the formation of reactive oxygen species and inflammation. We hypothesized that these processes can influence mitochondrial function of the placenta and fetus.Objective: We investigated the influence of PM10 exposure during pregnancy on the mitochondrial DNA content (mtDNA content) of the placenta and umbilical cord blood.Methods: DNA was extracted from placental tissue (n = 174) and umbilical cord leukocytes (n = 176). Relative mtDNA c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
191
3
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 209 publications
(200 citation statements)
references
References 51 publications
5
191
3
1
Order By: Relevance
“…It is noteworthy to mention that we observed an inverse correlation between placental mtDNA methylation and mtDNA content in contrast to a positive correlation observed in blood leukocytes. 22 Previous investigations have shown that mtDNA content is variable and fluctuates during aging, 31,32 under the influence of different environmental factors, 33 and the tissue investigated, 11,31,34 as well as different effects from recent versus long-term exposures. Nevertheless, we found similar results when we compared placental mtDNA content between mothers who continued smoking vs. non-smoking pregnant mothers (i.e., lower mtDNA content in smokers; relative difference of ¡21.98%, 95% CI: ¡41.10 to ¡0.86%, P D 0.01).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy to mention that we observed an inverse correlation between placental mtDNA methylation and mtDNA content in contrast to a positive correlation observed in blood leukocytes. 22 Previous investigations have shown that mtDNA content is variable and fluctuates during aging, 31,32 under the influence of different environmental factors, 33 and the tissue investigated, 11,31,34 as well as different effects from recent versus long-term exposures. Nevertheless, we found similar results when we compared placental mtDNA content between mothers who continued smoking vs. non-smoking pregnant mothers (i.e., lower mtDNA content in smokers; relative difference of ¡21.98%, 95% CI: ¡41.10 to ¡0.86%, P D 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…10 Changes in fetal mtDNA content may represent a biological effect along the path linking air pollution to effects on the fetus, such as birth weight. Previously, we showed a lower mtDNA content in placental tissue in association with in utero exposure to PM 10 (PM with aerodynamic diameter 10 mm), 11 which reflects signs of mitophagy and mitochondrial death.…”
Section: Introductionmentioning
confidence: 86%
“…PM 10 exposure increase in the last pregnancy month is associated with decrease in mtDNA content (Janssen et al 2012), and as a result, a decrease On the other hand, we recognize that an important number of studies showed that PM collected from different cities, including Ohio (Xu et al 2011), Washington, D.C. (Mutlu et al 2011), and Boston (Golomb et al 2012) in United States, Paris, (Ferecatu et al 2010), and Milan (Gualtieri et al 2009), among others, shares some mitochondrial disturbances. However, we cannot discard the fact that some of the mitochondrial effects observed in this work could be attributed partially to the specific-PM 10 composition collected from Mexico City.…”
Section: Discussionmentioning
confidence: 79%
“…These variations may be attributed to PM exposure during the gestation can increase the activity of glucocorticoid (Thomson et al 2013) suppressing the release of TSH (Wilber and Utiger 1969). Also, the antiinflammatory actions of glucocorticoids can induce the response of a systemic oxidative stress (Janssen et al 2012) and elevate the placental protein-bound 3-nitrotyrosine (Saenen et al 2016). Alternatively, PM2.5 can enter the lungs and blood circulation, where they may prompt the release of oxidative stress resulting in several neurodevelopment complications (Grahame et al, 2014).…”
mentioning
confidence: 99%